Design of 2 by 2 planar array antenna using aperture coupler technique / Hafiza Alias - Alias, Hafiza (2011)
This paper presents a design of 2 by 2 planar array microstrip antenna with a non-contacting feed. The type of non-contacting feeding used is aperture coupler technique. The antenna is basically consists of two layer of substrates which called superstrate and substrate. Patches are printed on top of the superstrate while the feedline is located on the bottom of the substrate. The antenna is designed at 5.8 GHz of frequency. The parameters in concern are the response of S11( which is the return loss, and the radiation pattern. The design is first being simulated in CST Microwave Studio and then fabricated onto FR-4 to see the actual antenna's performance.